Actualization of Religious Moderation in Islamic Fatwas in Mainstream Online Media in Indonesia - Asa’ari; Iskandar, Nuzul; Hainadri (JURNAL PENELITIAN, 2023)
In the context of Indonesia’s digital public sphere, Islamic fatwas disseminated through mainstream media play a pivotal role in shaping religious narratives. This study investigates the actualization of religious moderation within Islamic fatwas published by Republika Online, a prominent media outlet known for its Islamic orientation. The research aims to analyze how the values of religious moderation—as defined by Indonesia’s Ministry of Religious Affairs—are reflected in fatwa content, particularly in the areas of national commitment, tolerance, anti-discrimination, and cultural accommodation. This study employs a qualitative-descriptive design, combining media text analysis with field research and applies Teun A. van Dijk’s Critical Discourse Analysis (CDA)framework to unpack ideological structures behind fatwa discourse. The findings reveal that Republika’s fatwas tend to support religious moderation, especially in relation to national and anti-violence commitments. However, indicators such as cultural inclusivity and the recognition of latent forms of discrimination are frequently underrepresented. Furthermore, references to diverse Islamic legal traditions and local wisdom remain limited. This study contributes to understanding the dynamics of Islamic discourse in media and highlights the strategic role of fatwas in advancing religious moderation. It also offers critical insight for policymakers and media practitioners seeking to strengthen inclusive and context-sensitive religious communication.